NEITHER CREATED NOR DESTRUCTIBLE: IBN SINA ON THE ETERNITY OF THE UNIVERSE - Arif, Syamsuddin (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2020)
This article discusses Ibn Sīnā’s reasons for upholding the eternity of the world in his major philosophical writings and the ensuing heated debate between his detractors (al-Ghazālī, al-Shahrastānī and al-Rāzī) and supporters (al-Ṭūsī and al-Āmidī). I argue that notwithstanding the responses and surrejoinders it had elicited, Ibn Sīnā’s position on the issue is indeed coherent and irrefutable, since he distinguishes three modes of eternity, corresponding to the hierarchy of beings which he introduced, namely, (i) absolutely eternal (by virtue of itself); (ii) relatively eternal (by virtue of something else); and (iii) not eternal both considered per se as well per aliud. With this distinction he evades both horns of the dilemma: either the universe is eternal or it is not eternal. On Ibn Sīnā’s account, therefore, the universe is both eternal and not eternal. It is eternal because the efficient cause that necessitates and sustains its existence is eternal, but also not eternal in view of its essential contingency.